THE IMPLEMENTATION OF CREATIVE WRITING ON ELT (ENGLISH LANGUAGE TEACHING) TO INSPIRE SENIOR HIGH SCHOOL STUDENTS’ WRITING ACTIVITIES IN ELEVENTH GRADE OF MAN 2 PONOROGO IN ACADEMIC YEAR 2017/2018 - Novia Ella Febriana; Bambang Harmanto; Ana Maghfiroh (Universitas Muhammadiyah Ponorogo, 2018)
This purpose of this thesis is describing the effect of the implementation of creative writing on ELT (English Language Teaching) to inspiring the students’ writing activities in Eleventh Grade of MAN 2 Ponorogo in Academic Year 2017/2018.The subject of this research is the student of Eleventh Grade of MAN 2 Ponorogo. This research provide classroom action research method which doing the observations about the students’ writing learning activities before and after the research and monitoring the development of the students’ tasks by guiding them in creative writing. The researcher also makes the interview with the students’ experienced when they’re conducting writing activities. The data comes from students’ interviews and observation conducts to students’ writing paper, which one that they are finding problems in finding ideas than the other students within their understanding to find the ideas. This study will show you how creative writing will improve the students’ ideas and also provide their abilities to stay in their way of writing; they can also find their style in writing. Creative writing also produce their energy in order to find new discovery in the topic they had been chosen. It also guide them to be discipline, confident, imaginative, be a planner, because they will make their deadline a project of writing, they also try to be a pioneer, not a plagiarism. The researcher suggestion about this research were the student should read intensively to increase their vocabularies, doing the example of the task for more understanding about the lesson, and the last the teacher should apply the various the teaching method to motivate the student in learning English.